Media trends : presentations of women and children in the Guyanese media 2008-2009 - Mohamed, Paloma (UNICEF Guyana & Guyana. Ministry of Labour... GeorgetownGY, 2009)
Analyses representation of women and children's issues in the media in Guyana.